Control of Trachoma from Achham District, Nepal: A Cross-Sectional Study from the Nepal National Trachoma Program. - Bidya Prasad Pant; Ramesh C Bhatta; J S P Chaudhary; Suresh Awasthi; Sailesh Mishra; Shekhar Sharma; Puja A Cuddapah; Sarah E Gwyn; Nicole E Stoller; Diana L Martin; Jeremy D Keenan; Thomas M Lietman; et al. (Public Library of Science (PLoS), 2016)
The WHO seeks to control trachoma as a public health problem in endemic areas. Achham District in western Nepal was found to have TF (trachoma follicular) above 20% in a 2006 government survey, triggering 3 annual mass drug administrations finishing in 2010. Here we assess the level of control that has been achieved using surveillance for clinical disease, ocular chlamydia trachomatis infection, and serology for antibodies against chlamydia trachomatis protein antigens.We conducted a cross-sectional survey of children aged 1-9 years in communities in Achham District in early 2014 including clinical examination validated with photographs, conjunctival samples for Chlamydia trachomatis (Amplicor PCR), and serological testing for antibodies against chlamydia trachomatis protein antigens pgp3 and CT694 using the Luminex platform.In 24 randomly selected communities, the prevalence of trachoma (TF and/or TI) in 1-9 year olds was 3/1124 (0.3%, 95% CI 0.1 to 0.8%), and the prevalence of ocular chlamydia trachomatis infection was 0/1124 (0%, 95% CI 0 to 0.3%). In 18 communities selected because they had the highest prevalence of trachoma in a previous survey, the prevalence of TF and/or TI was 7/716 (1.0%, 95% CI 0.4 to 2.0%) and the prevalence of ocular chlamydia trachomatis infection was 0/716 (0%, 95% CI 0 to 0.5%). In 3 communities selected for serological testing, the prevalence of trachoma was 0/68 (0%, 95% CI 0 to 5.3%), the prevalence of ocular chlamydia trachomatis infection was 0/68 (0%, 95% CI 0 to 0.5%), the prevalence of antibodies against chlamydia trachomatis protein antigen pgp3 was 1/68 (1.5%, 95% CI 0.04% to 7.9%), and the prevalence of antibodies against chlamydia trachomatis protein antigen CT694 was 0/68 (0%, 95% CI 0 to 5.3%).This previously highly endemic district in Nepal has little evidence of recent clinical disease, chlamydia trachomatis infection, or serological evidence of trachoma, suggesting that epidemiological control has been achieved.